Art, science and technology, brief reflections on interdisciplinary work (2018)
Interdisciplinary work is necessary to respond to the challenges of the current society. For instance, the partnership between technology, humanities and arts, had allowed the contemporary development of interactive systems. An example is the fact that producing a smartphone involves graphic designers, psychologists, illustrators, sociologists, and other professionals, including engineers. One might say the same about the development of video games, laptops, movies and computer mice. In summary, behind of the creation of any "technological artifact" there is hard interdisciplinary work.